Orbitrap™-SIMS analysis of advanced semiconductor inorganic structures. (August 2022) - Franquet, A.; Spampinato, V.; Kayser, S.; Vandervorst, W.; van der Heide, P.
Abstract: Shrinking semiconductor device dimensions requires extensive R&D in all areas, inclusive of the materials characterization techniques and methodologies commonly used. With dimensions now being much smaller than the beam spot sizes of usual characterization methods like SIMS, RBS, etc., new concepts are needed. In this context, the application of Self-Focusing SIMS (SF-SIMS) to determine the bulk composition of structures of exceedingly small dimensions was demonstrated in the past years. However, due to the extensive use of secondary ions of higher m/z in the SF-SIMS concept, high mass resolution is often required; this is to avoid possible mass interferences that limit the SF-SIMS method to reach low detection limits and/or to unambiguously identify the ion signals. Although the mass resolving power of Time-of-Flight (ToF) analyzers of SIMS instruments is considered high ( m /Δ m ∼10000), it still presents a restriction for the SF-SIMS methodology on specific systems. The Orbitrap™ mass analyzer allows an increase in the mass resolution up ∼20x along with mass accuracy levels below one ppm. In this study, we demonstrate that the mass resolving power of the Orbitrap™-SIMS allows to resolve limiting mass interferences, thereby allowing accurate quantification of impurities/dopants in small finFET structures (<20 nm). Graphical abstract: Image 1 Highlights: Self-Focusing SIMS approach enables the analysis of confined volumes. Hybrid SIMS (Orbitrap mass analyzer) analysis of inorganic microelectronic systems. Dopant quantification in narrow trenches using ToF-SIMS and Hybrid SIMS.